Configure and Monitor the Networking Using EIGRP Protocol - Azman, Anis Zahirah; Mahamad, Abd Kadir; Saon, Sharifa; Hamzah, Shipun Anuar; Md Noor, Danial (Journal of Electronic Voltage and Application, 2021)
In this modern internet generation, routing protocol plays an important role. The Enhanced Interior Gateway Routing Protocol (EIGRP) is an advanced protocol for distance-vector routing used on a computer network to simplify routing and configuration decisions. Data packets are transmitted from router to router via internet networks before they reach their destination device on the Internet. The main objective of this paper is to configure and monitor the network by the provider. The protocol implemented, EIGRP is analyzed using the GNS3 software. In GNS3 software, the setup includes routers and hosts is simulated to display a network that consists of three areas. It analyzed the ping test, display neighbours and topology table, and the number packet received and sent. As a result, the simulated protocol, EIGRP show acceptable performance with hellos sent/received packets are 3544/1766, 144/143 and 6383/2107 of a router; R1, R2, and R3 respectively. In conclusion, EIGRP is the best in routing protocol and provide excellent internetworking.